Weston Leonard

2023-03-02

How to use the square root property to solve this equation ${(2x+3)}^{2}=25$?

Mikaela Horn

Beginner2023-03-03Added 6 answers

By obtaining the square root of both terms on either side of the equation, the square root property is demonstrated.

Doing the same for the specified equation

$\sqrt{{(2x+3)}^{2}}=\sqrt{25}$

$\sqrt{25}={\pm 5}$

So,

$\sqrt{{(2x+3)}^{2}}={\pm 5}$

$(2x+3)={\pm 5}$

First solution:

$2x+3=+5$

Isolating $x$

$2x+3-{3}=+5-{3}$

$2x=2$

$x=1$

Second solution:

$2x+3=-5$

Isolating $x$

$2x+3-{3}=-5-{3}$

$2x=-8$

$x=-4$

Doing the same for the specified equation

$\sqrt{{(2x+3)}^{2}}=\sqrt{25}$

$\sqrt{25}={\pm 5}$

So,

$\sqrt{{(2x+3)}^{2}}={\pm 5}$

$(2x+3)={\pm 5}$

First solution:

$2x+3=+5$

Isolating $x$

$2x+3-{3}=+5-{3}$

$2x=2$

$x=1$

Second solution:

$2x+3=-5$

Isolating $x$

$2x+3-{3}=-5-{3}$

$2x=-8$

$x=-4$